Государство и эволюция: художественная лит-ра / Е. Гайдар - Гайдар Егор (Центр книги Рудомино, 2014)
Экземпляры: аб. (20141010) / Инвентарный номер: 50507 / Цена: 280. 00. / Сис.шифр: 66(0) / Авт.знак: Г 14 / ГРНТИ: 11.15 / ББК: 66(0)